The Influence Of Firm Size, Profitability, Leverage, And Kap Reputation On Audit Delay (Empirical Study on Manufacture Firms Food and Beverages Sub Sector Listed on the Indonesia Stock Exchange 2017-2019) - Jessica Iglasias Gunawan (Global Accounting, 2022)
There has been an increase in the number of Firms listed on the Indonesia Stock Exchange (IDX) since 2017 – 2019 which was accompanied by an increase in Indonesia's Gross Domestic Product (GDP) in the same period. The IDX requires issuers to provide audited financial reports. This will increase the number of financial reports to be audited. The audited financial report must be submitted no later than the end of the 3rd month after the date of the annual financial report and if it is late, it will be subject to sanctions. This makes audit delay important. This study aims to assess the effect of Firm size, profitability, leverage, kap reputation towards audit delay. The research used food and beverage Firms listed on IDX from 2017-2019 for research sample. Total of Firms used for sample research is 12 thus total sample become 36. The amount got by doing purposive sampling towards 27 Firms. The research obtains Firm’s size variable, profitability, leverage, and kap reputation have a significantly effect on audit delay. Firm size, profitability, leverage and kap reputation simultaneously have a significant effect towards audit delay.